Real‐time shimming with FID navigators - Wallace, Tess E.; Kober, Tobias; Stockmann, Jason P.; Polimeni, Jonathan R.; Warfield, Simon K.; Afacan, Onur (Magnetic resonance in medicine, 2022)
Purpose To implement a method for real‐time field control using rapid FID navigator (FIDnav) measurements and evaluate the efficacy of the proposed approach for mitigating dynamic field perturbations and improving T2*$$ T_2^{* } $$‐weighted image quality. Methods FIDnavs were embedded in a gradient echo sequence and a subject‐specific linear calibration model was generated on the scanner to facilitate rapid shim updates in response to measured FIDnav signals. To confirm the accuracy of FID‐navigated field updates, phantom and volunteer scans were performed with online updates of the scanner B0 shim settings. To evaluate improvement in T2*$$ T_2^{* } $$‐weighted image quality with real‐time shimming, 10 volunteers were scanned at 3T while performing deep‐breathing and nose‐touching tasks designed to modulate the B0 field. Quantitative image quality metrics were compared with and without FID‐navigated field control. An additional volunteer was scanned at 7T to evaluate performance at ultra‐high field. Results Applying measured FIDnav shim updates successfully compensated for applied global and linear field offsets in phantoms and across all volunteers. FID‐navigated real‐time shimming led to a substantial reduction in field fluctuations and a consequent improvement in T2*$$ T_2^{* } $$‐weighted image quality in volunteers performing deep‐breathing and nose‐touching tasks, with 7.57% ± 6.01% and 8.21% ± 10.90% improvement in peak SNR and structural similarity, respectively. Conclusion FIDnavs facilitate rapid measurement and application of field coefficients for slice‐wise B0 shimming. The proposed approach can successfully counteract spatiotemporal field perturbations and substantially improves T2*$$ T_2^{* } $$‐weighted image quality, which is important for a variety of clinical and research applications, particularly at ultra‐high field.